Microlearning untuk Produksi Ragam Learning Object Materials - Ariani, Diana; Prawiradilaga, Dewi Salma; Fatharani, Wasetya (Jurnal Pembelajaran Inovatif, 2022)
E-learning or online learning are more attractive these days, so competence is needed in developing learning object materials (LOM), but the ability to LOM is not widely owned by developers. The Education Technology Study Program has a graduate profile, among others, as a developer of learning media for innovative types of learning, one of which is able to develop a variety of LOM according to the needs of online learning or e-learning. To achieve these needs by developing Microlearning regarding the production steps of various LOM. Microlearning development were chosen because students are currently experiencing changes in learning styles, which tend to access and enjoy learning materials that have a short duration, focus or contain direct exposure that is in accordance with learning objectives, and can be accessed by mobile. This study uses the Rapid Prototyping Model with 5 stages: Assess Needs and Analyze Content, Set Objectives, Construct Prototype (design), Utilize Prototype (research), and Installing and Maintain System. From this stage, this research has publication outputs in national journals, Gamification products and IPR. Abstrak E-learning ataupun online learning yang semakin diminati, maka dibutuhkan kompetensi dalam mengembangan learning object materials (LOM), namun kemampuan mengembangkan LOM belum banyak dimiliki oleh para pengembang. Program Studi Teknologi Pendidikan memiliki profil lulusan antara lain sebagai pengembang media pembelajaran untuk jenis pembelajaran inovatif, salah satunya mampu untuk mengembangkan ragam LOM sesuai kebutuhan pembelajaran online atau elearning. Upaya yang dilakukan adalah dengan mengembangan Microlearning mengenai langkah produksi ragam LOM. Upaya pengembangan Microlearning dipilih dikarenakan, peserta didik saat ini sudah mengalami perubahan gaya belajar, yaitu cenderung mengakses dan menikmati bahan belajar yang memiliki durasi singkat, fokus atau berisi paparan langsung yang sesuai dengan tujuan pembelajaran, serta dapat diakses dengan mobile. Penelitian ini menggunakan Model Rapid Prototyping dengan 5 tahapannya, yaitu : Assess Needs and Analyze Content, Set Objectives, Construct Prototype (design), Utilize Prototype (research), dan Installing and Maintain System. Dari tahapan tersebut, penelitian ini memiliki Luaran publikasi pada jurnal nasional, produk Gamifikasi dan HKI.